Magnetostratigrafhy and Depositional Sequence analysis of Triassic Fluvial Sedirnents: UK Central North Sea. - Brid, D.J.; Chandler, P.; Turner, P.; Heywood, M.L. (Cuadernos de Geología Ibérica, 1996)
The stratigraphy and depositionai history of the Triassic of the 11K Central North Sea has been studied using a combination of litho and magnetostratigraphic techniques. Depositional sequences aud facies eyele wedges represent major phases of alluvial plain/lacustine progradation and retrogradation. Three main sequenee sas, named TRI, TR2 and TR3 are recognised in which the peak retrogradation boundaries are identffied at the high gamma apex on upwaird-fining profiles, In order to test the ehronostratigraphic significance of flie lake margin lboding surfaces a detailed magnetostratigraphic study of the TR2/TR3 boundary has been undertaken in five wells from the Mamock, Drakc, Fiddieh aud Skua fields. The resulis indicate that significant improvements can be made to these correlation sehemes which are based oil hthofacies stacking patterns interpreted from core and wireline bog responses. The resulis indicate that the TR2/TR3 approximates cbosely fo a chronostratigraphic boundary, at least on a field wide seale.